A novel checkpoint mechanism regulating the G1/S transition - Tvegård, Tonje (Cold Spring Harbor Laboratory Press, 2007)
Ultraviolet irradiation of fission yeast cells in G1 phase induced a delay in chromatin binding of replication initiation factors and, consistently, a transient delay in S-phase entry. The cell cycle delay was totally dependent on the Gcn2 kinase, a sensor of the nutritional status, and was accompanied by phosphorylation of the translation initiation factor eIF2α and by a general depression of translation. However, the G1-specific synthesis of factors required for DNA replication was not reduced by ultraviolet radiation. The cell cycle delay represents a novel checkpoint with a novel mechanism of action that is not activated by ionizing radiation.